2019
DOI: 10.1097/rhu.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Identification of Risk Factors of Uveitis in Juvenile Idiopathic Arthritis

Abstract: Background Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease of childhood. The JIA–associated uveitis represents the most common extra-articular manifestation. Objectives The main aim of this study was to evaluate frequency and risk factors of uveitis in a pediatric population affected by JIA. Methods One hundred eight Italian children with JIA were followed during a follow-up period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…When only considering patients from the moment at which a biological was prescribed onwards, patients with oligoarticular ANA+ JIA and polyarticular RF+ JIA were found to have the highest mean annual duration of biological use. However, as biologicals are currently not registered for oligoarticular ANA+ JIA, the high duration of biological use in this subgroup (n = 22) is likely attributable to treating JIA-related uveitis, as this JIA subgroup has the highest risk of developing uveitis [28]. When considering this subgroup in detail it is observed that the mean duration of follow-up is 4.8 years, of which they receive a biological for on average 2.2 years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When only considering patients from the moment at which a biological was prescribed onwards, patients with oligoarticular ANA+ JIA and polyarticular RF+ JIA were found to have the highest mean annual duration of biological use. However, as biologicals are currently not registered for oligoarticular ANA+ JIA, the high duration of biological use in this subgroup (n = 22) is likely attributable to treating JIA-related uveitis, as this JIA subgroup has the highest risk of developing uveitis [28]. When considering this subgroup in detail it is observed that the mean duration of follow-up is 4.8 years, of which they receive a biological for on average 2.2 years.…”
Section: Discussionmentioning
confidence: 98%
“…Patients were classified into JIA subtype according to the ILAR criteria [17]. As persistent oligoarticular JIA was the most common subtype, and because the risk of developing JIArelated uveitis depends on a patient's antinuclear antibody (ANA) status [28], this subtype was further subdivided into ANA-oligoarthritis and ANA+ oligoarthritis. The duration of medication use and accompanying costs were calculated for all JIA patients in general and by JIA subtype.…”
Section: Discussionmentioning
confidence: 99%
“…A signi cant higher frequency of ANA positive patients was observed in the JIA-U group (72.2%) (p = 0.0157). Moreover, in 83.3% of our cases, the diagnosis of JIA preceded the ocular involvement, and we observed a signi cant correlation between uveitis onset and younger age at JIA diagnosis [13,[22][23][24][23][24][25]. Calandra et.…”
Section: Discussionmentioning
confidence: 72%
“…In regards to risk stratification of JIA, autoantibodies are useful. A positive ANA has clinical implications as it is a risk factor for the development of uveitis [35,36,39]. As previously mentioned, frequent ophthalmologic screening is needed to detect asymptomatic uveitis [38].…”
Section: Laboratory Work-upmentioning
confidence: 99%
“…Regular ophthalmological screening is recommended for all children with JIA [38]. Children with risk factors for uveitis, including female gender, oligoarthritis, younger age of JIA onset and Anti-Nuclear Antibody (ANA) positivity, should undergo more frequent ophthalmological screening [35,36,39]. Beyond arthritis and uveitis, psoriatic arthritis can also present with psoriasis, as its name suggests.…”
Section: Extraarticular Manifestationsmentioning
confidence: 99%